Notation and Drawing of Holy Qur’an: a sign of Deletion of the Specific Letter "Alif" in the Writing of Holy Quran (Jamahiriya Edition) (Abhat Journal, 2023)
This research dealt with the most prominent characteristics , features of collecting and notation of the holy Quran and I attempted  to present the Topic from subtle  Aspect to reach the desired benefit  and they are as follows : summarizing the reasons For each combination and indicating its characteristics avoiding the researching Frequency and in order to reach the heart of the topic so the reader can reach it owing The full Idea about  topic of collecting and notation the holy Quran which is  Notated the Jamahiriya Mus'haf and studying that is Unique to it in drawing of  In Jamahiriya Mus'haf which is the use special sign to delete the letter Alif And we will discuss the saying in details , its place and in Terms of the origin of  Naming , purposes of  its use and its reasons .              This raised several questions from the specialists between the denier and the permissible Hoe ever we are nothing than we are researching this issue using the scientific research to remove the ignorance from our selves. perhaps someone who studies or researches Perhaps will find answer for his Questions and the most Important source that we have Resorted on the subject of Uniqueness of Jamahiriya Mus'haf ' drawing with the sign of Deleting the letter Alif (allocated) are the scholars and the Sheikhs who learned in this Specialization and then Jamahiriya Mus’haf margin and the basic written source in this Aspect.
Keywords: Quran notation; Othman collection; Quran's drawing